COMPARISON OF EDENTULOUS WOMEN AND DENTATE WOMEN IN TERMS OF MANDIBULAR ALVEOLAR RIDGE HEIGHT REVIEWED USING PANORAMIC RADIOGRAPHY - Manja, Cek Dara; Abkharina, Shanaya (Faculty of Dentistry, Mahasaraswati Denpasar University, 2020)
When tooth loss occurs, the absence of mechanical stimulus on alveolar ridge, the decline occurred because the height of the alveolar ridge undergoes a slow physiological resorption. The purpose of this research is to know the difference and the average height of the mandibular alveolar ridge in edentulous and dentate women using panoramic radiography. The method of this research is an analytical method with cross-sectional approach. Total sample of 40 women, edentulous and dentate has been measured. Measurements were made by measuring the distance between the lowest point of mandibula and alveolar crest mandibula on the incisor point, right and left premolar, right and left molar. Statistical test is done using independent t test. The results showed that the average value of a dentate women sample is greater than edentulous. Average value obtained by the dentate sample is greatest in right premolar point by 29,53 mm ± 2,36 mm and the smallestat the left molar point by 25,48 mm ± 2,41 mm. Average value obtained by the edentulous sample is greatest in right molar point by 22,26 mm ± 3,67 mm and the smallest at the left premolar point by 21,21 mm ± 4,79 mm. It can be concluded that there is a significant difference in the height of the mandibular alveolar ridge on edentulous sample and dentate in everypoint of measurement. The average height of the mandibular alveolar ridge in edentulous sample is 21,78 mm ± 3,88 mm and the dentate sample is 27,71 mm ± 2,77